2017
DOI: 10.1039/c6ta07098a
|View full text |Cite
|
Sign up to set email alerts
|

Framework-mediated synthesis of highly microporous onion-like carbon: energy enhancement in supercapacitors without compromising power

Abstract: A new pathway to onion-like carbon with narrow, regular and connected pores overcomes the trade-off between power delivery and energy storage capacity in supercapacitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…Also, a microporous onion‐like carbon (MOLC) was prepared by direct carbonization of a diamond‐like porous aromatic framework (PAN‐1). [ 175 ] It was found that SSA and the fraction of small micropores (0.5 nm) decreased with elevated pyrolysis temperatures. The optimal MOLC showed a curved graphitic structure with an SSA of 1084 m 2 g −1 and micropores peaked at sizes of 0.5, 1.2–1.3 nm, demonstrating a supercapacitor capacitance of 211 F g −1 at 5 mV s −1 .…”
Section: Microporous Carbon Nanostructurementioning
confidence: 99%
“…Also, a microporous onion‐like carbon (MOLC) was prepared by direct carbonization of a diamond‐like porous aromatic framework (PAN‐1). [ 175 ] It was found that SSA and the fraction of small micropores (0.5 nm) decreased with elevated pyrolysis temperatures. The optimal MOLC showed a curved graphitic structure with an SSA of 1084 m 2 g −1 and micropores peaked at sizes of 0.5, 1.2–1.3 nm, demonstrating a supercapacitor capacitance of 211 F g −1 at 5 mV s −1 .…”
Section: Microporous Carbon Nanostructurementioning
confidence: 99%
“…The high explicit surface zone, enormous pore volume, well-requested and controllable permeable structure, unique morphologies of carbons and their outstanding chemical, mechanical and warm dependability make them fascinating for remarkable applications including catalysis, energy storage and change, water purification and sensing. [9][10][11][12][13][14][15][16][17][18]Varity of carbon material having excellent capacitance behaviour like carbon onion [19], carbide-derived carbon [20], carbon aerogels [21], carbon nanotube [22] outstanding retentivity of the electrode material [23]. Carbon sphere contains more advantages compare to exhausting material like spherical geometry, good liquidness, controllable porosity and ultra-tuneable size.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of OLC nanostructures show very interesting physicochemical properties that are attractive for SCs. For example, Majumder et al [12] reported a microporous onion-like carbon (MOLC) structure carbonized from diamond-like porous aromatic framework (PAF) via a onestep method (Fig. 1a-e).…”
Section: Carbon Onionsmentioning
confidence: 99%
“…e HRTEM images of the PAF-1-derived carbon at 900°C. d TEM image of OLC, that is, the fully transformed detonation diamond powder (Reprinted with permission from [12,72]. Copyright 2017, Royal Society of Chemistry.…”
Section: Carbon Fibersmentioning
confidence: 99%
See 1 more Smart Citation